ISLAMIC RELIGIOUS EDUCATION LEARNING MANAGEMENT BASED ON THE SUNNAH VALUES OF PROPHET MUHAMMAD ﷺ IN SHAPING ISLAMIC SCHOOL IDENTITY AT ALHAZEN SCHOOL BINTARO - Irfan Kuncoro (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study examines Islamic Religious Education learning management based on the Sunnah values of Prophet Muhammad ﷺ in shaping Islamic school identity at Alhazen School Bintaro. The background of this study lies in the challenge faced by modern Islamic schools in preserving prophetic values amid the influence of popular culture, secular learning orientations, and formalistic religious instruction. Islamic education should not only transmit religious knowledge, but also manage adab, worship habituation, teacher exemplary conduct, and school culture as an integrated learning system. This research employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with school leaders and teachers, and documentation of learning activities and school culture. The findings show that Islamic Religious Education learning management at Alhazen School Bintaro integrates Sunnah values through teacher and student adab, morning dhikr, Qur’anic muraja’ah, worship habituation, Islamic verbal expressions, teacher role modelling, classroom discipline, and a spiritually oriented learning environment. The internalization process is implemented through habituation, exemplary conduct, Islamic environmental culture, cultural filtering, and collective religious activities. This study concludes that Sunnah-based Islamic Religious Education learning management strengthens Islamic school identity by connecting knowledge, worship, adab, character formation, and institutional culture into daily educational practices.